PREPARASI BETON POLIMER BERBASIS SLUDGE – ABU TERBANG DAN KARAKTERISASINYA - Perdamean Sebayang; Muljadi Muljadi; Deni S Khaerudini; Anggito P Tetuko1 (Jurnal Ecolab, 2009)
Polymer concrete has been made using fly ash and sludge waste for raw material bases, and epoxy resin was used asbinder material. The sludge raw material was dried and crushed until fine powder morphology, then the fly ash wascrushed again until through out 100 mesh and it blended until became homogeneous mixing materials. The rawmaterial compositions where added with epoxy resin, that is: 10 and 15 % from the total weight of raw material. Thesample testing was made by hand press method with dimension: 4 x 4 x 16 cm3. The testing of samples included:density, water absorption, fire resistance, compressive, and bending strength. Microstructure analysis was usedScanning Electron Microscope (SEM) method. The results show that polymer concrete based on fly ash - sludge andepoxy resin binder is properly moderate, if it is compared to conventional concrete. The best result has the compositionof 60 % fly ash, 40 % sludge, and 15 % epoxy resin (% weight) composition, with its characteristics: density= 1.93 g/cm3, water absorption = 0.74 %, compressive strength = 28 MPa, and bending strength = 12.8 MPa. Thepolymer concrete that has been made is suitable for building material application, especially in the water or submergedarea, and it also has light weight concrete specification.